Central Bank Foreign Exchange Market Intervention and Option Contract Specification : The Case of Colombia - Mandeng, Ousmene (IMF Working Papers; Working Paper ;, 2003)
This paper aims to identify appropriate option contract specifications for effective central bank exchange market intervention. Option contract specifications determine the impact of options on the underlying asset or currency, and hence their actual effect on asset price or currency volatility and are therefore key to determining the effectiveness of option-based intervention. The paper reviews the experience of the systematic option-based foreign exchange market intervention of the Central Bank of Colombia and finds that its contract has only been moderately successful at abating exchange rate volatility, which is attributed here to sub-optimal contract specifications.